Hierarchical Composite of Sb2S3 decorated on highly crumpled Ti3C2Tx nanosheets for enhanced sodium storage properties. (20th March 2021) - Ren, Mingxi; Cao, Dong; Jiang, Wei; Su, Kai; Pan, Limei; Jiang, Yuhang; Yan, Shanshan; Qiu, Tai; Yang, Meng; Yang, Jian; Zhang, Chuanfang (John)
Highlights: Nano Sb2 S3 decorated crumpled Ti3 C2 Tx was prepared by a scalable wet-chemistry method. Co-initiation of HCl-Sb 3+ & freeze-drying produce highly-crumpled Ti3 C2 Tx nanosheets. Synergies of Sb2 S3 nanoparticles and Ti3 C2 Tx nanosheets form a 3D porous architecture. Fast electron/Na + transport and relieved agglomeration/volume-expansion were achieved. A high capacity of 215 mAh g −1  at 2 A g −1, maintaining 118 mAh g −1  after 500 cycles. Abstract: Hierarchical composites with good electrical conductivity and sufficient voids are in great demand for the high-performance storage of sodium ions but typically limited due to the complicated synthesis procedure. Here, we report on a facile wet-chemistry synthesis of Sb2 S3 nanoparticles onto highly crumpled Ti3 C2 Tx nanosheets, which form three-dimensional (3D) architecture with good electrical conductivity. The homogeneously distributed Sb2 S3 nanoparticles suppress the restacking issue of the Ti3 C2 Tx nanosheets, which creates rich voids for rapid electron/Na + transport and minimizes the volume expansion effect from Sb2 S3 upon repeated charging/discharging cycles. When used as a sodium-ion battery (SIB) anode, the composite shows a high capacity (329 mAh g −1 at 100 mA g −1 after 100 cycles) and good rate capability and cycling performance (215 mAh g −1 at 2 A g −1 and maintains 118 mAh g −1 after 500 cycles). We believe the metallic interconnected network and the 3D architecture synergistically result in a promoted sodium-ion storage performance. This work provides a simple strategy to construct MXene-based hybrids with a porous network structure for application fields, such as energy storage, photocatalysis, adsorption, and microwave absorption.